Arabic Literacy for Strengthening Islamic Education at the Pondok Pesantren Darullughah Wadda’wah - Samsul Huda (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Islamic education in Indonesia is closely linked to Arabic language literacy, particularly in pesantren, which plays a significant role in developing an understanding of Islamic values. However, the challenges in strengthening Arabic language literacy remain an issue that needs to be addressed, especially concerning santri interest and teaching methods. This study aims to explore the efforts to strengthen Arabic language literacy in the context of Islamic education at Pondok Pesantren Darullughah Wadda’wah. The research method employed in this study is a qualitative approach with a case study design. The results show that Pondok Pesantren Darullughah Wadda’wah has programs that focus on improving knowledge of the Qur’an, language skills, da’wah abilities, and combining formal and informal education. Additionally, the education at the pesantren places a strong emphasis on spiritual aspects through worship activities. With this holistic approach, the pesantren successfully creates a learning environment that supports the mastery of Arabic language literacy. This research contributes significantly to the model for developing Arabic language literacy within the context of Islamic education in educational institutions.